PERBANDINGAN BEKSAN LAWUNG AGENG DALAM PERNIKAHAN AGUNG TAHUN 2013 DENGAN PERINGATAN 30 TAHUN BERTAHTA SRI SULTAN HAMENGKU BUWONO X TAHUN 2019 DI KARATON NGAYOGYAKARTA HADININGRAT : KAJIAN ASPEK MAKNA, BENTUK, DAN FUNGSI - Kristianto, Riki; Kuswarsantyo, Kuswarsantyo (Jurnal Seni Tari, 2020)
This study aims to compare the similarities and differences of Beksan Lawung Ageng in marriage between GKR Hayu and KPH Notonegoro in 2013 with those displayed on the 30th anniversary of Sultan Hamengku Buwono X's year 2019. Qualitative research methods and ethnocoreology were used in this study with analytical descriptions other than using hermeneutics which is a theory of interpretation also uses ethnochoreology, history, sociology, anthropology and semiotics approaches. Data collection techniques using observation, interviews, and study documentation. Data analysis is performed through data reduction, data presentation, and conclusions. Test the validity of the data by triangulation. The results of this study indicate that there are changes and differences in the function and form of the Beksan Lawung Ageng at GKR Hayu's marriage to KPH Notonegoro in 2013 with the 30th anniversary of Sultan Hamengku Buwono X's throne. Besides, there are also factors and reasons for changes in function and differences. the form of Beksan Lawung Ageng at the wedding of GKR Hayu with KPH Notonegoro in 2013 and Beksan Lawung Ageng at the 30th anniversary of Sultan Hamengku Buwono X's reign which revealed the Ngayogyakarta Hadiningrat Karaton policy in the era of Sultan Hamengku Buwono X in the protection and development of dance heirlooms.    Keywords: Lawung Ageng dance, Yogyakarta classical dance, Yogyakarta palace, royal wedding, accession to the throne